Estudo sobre a toxicidade da Aspidosperma pyrifolium (pereiro) - Lima, Maíra Conceição Jeronimo de Souza (2011)
This study aimed to evaluate the spontaneous cases of poisoning in goats, rats and toxicity in vitro cytotoxicity of Aspidospema pyrifolium. In all spontaneous cases studied, the plant is ingested and the abortion cases occurred exclusively in goats. Most cases of abortion occurred during the dry season and early rainy season, and experienced the goats were less affected than the young goats. We used male and female rats of Wistar strain. The extract of the plant A. pyrifolium was administered in females at day 15 of gestation or from the 15th to the 17th day of gestation, which showed reduced fetal weight and strong evidence of maternal toxicity. Rats subjected to intraperitoneal injection of the extract of A. pyrifolium showed motor dysfunction and death, male rats were more resistant than females. The administration of atropine, diazepam and xylazine did not help in preventing the effects of toxicity. The evaluation of osmotic fragility of red blood cells was performed with the plant extract in different concentrations. In addition, we used larvae from a day of brine shrimp, which were incubated with different concentrations of the extract. It was found that the extract of A. pyrifolium promoted hemolysis and was lethal to A. saline. These in vitro tests may be useful as adjunct tests for further studies with this plant.